Princess Ben : being a wholly truthful account of her various discoveries and misadventures, recounted to the best of her recollection, in four parts - Murdock, Catherine Gilbert (Graphia/Houghton Mifflin Harcourt, 2008)
Princess Benevolence discovers an enchanted room while locked in the castle's highest tower by the conniving Queen Sophia and begins learning the magical arts, which may help her save her kingdom from a mortal threat.